Fortaleza, uma cidade negra na “Terra da Luz”: ensino de história e memórias do pós-abolição no enfrentamento à invisibilização afrocearense - Barreto, Héctor Cândido Oliveira (2023)
This dissertation aimed to investi gate the fo rmation of a social memo ry and its epresentations about slavery and post abolition Ce ará from the analysis and problematizati on of the speeches published in the journal of the Historical Institute of Ceará in 1984, the first centennial of the a bolition of slavery in Ceará and which mpacted on a whiteness oriented teaching of Ceará's his to ry. A hegemonic narrative t hat, when not invisibilized, disqualified the soci al function of the black as much as it stigmatized him, associating him to slavery , subservie nce and intellectual incapacity almost as aninherent relationship. Contributing to the (re)production of a schoo l historical now ledge based on racial discourses present in this pro duction, affirming a racialized istoriography that sponsored a memorializ ation about the blacks from Ceará linked to slavery, structuring an image of racial in feriorization and of a victimized, vexatious, humiliating identity intrinsica llyrelated to slavery. The research developed in the problematization of the structur ing of a local racism that cros sed all these points, producingin its core, a literacy through education, embedded with racial segregation and a kind of natural inferiority relegated to bla ck people. Through a proposal of education for ethno racial relations, we weave ideological confrontations with the constitution of Western paradigms that have promoted the naturalization of the estrangement of blackness in our classroom s. Finally, we propose a didactic sequence through class workshops that aims the mapping of the black fortress from a bank of Afro Brazilian references de veloped by students of public basic education, which maybe represented: communities, characters, events and black so ciabilities in the city of Fortaleza. It is a guiding material for classro om work in the approach to concepts such as memory and history of slavery and post a bolition, identities, racism and territorialities, bringing to the visible black collectives, subjects and sociabilities, daily invisibilized and being contribut ory to mapping and representativeness in the proposed field.